Effects of calcium supplementation on the prevention of preeclampsia: an umbrella review of systematic reviews and meta-analyses - Henok Kumsa; Esuyawkal Mislu; Mulugeta Wodaje Arage; Biruk Beletew Abate; Biruk Beletew Abate; Moges Beriye; Mihretab Mehari Reda; Nigus Bililign Yimer (Frontiers in Medicine)
BackgroundPreeclampsia is the leading cause of maternal and fetal morbidity and mortality. Calcium supplementation has been considered a potential intervention to reduce the risk of preeclampsia. This umbrella review aims to summarize the effects of calcium supplementation in the prevention of preeclampsia based on existing systematic reviews and meta-analyses studies.MethodsA systematic search of electronic databases, such as MEDLINE, Web of Science, SCOPUS, and the Cochrane Library, was conducted from inception to 30 December 2023. The methodological quality of the included studies was assessed using the revised version of the Assessing the Methodological Quality of Systematic Reviews (AMSTAR 2) tool. A random-effects model was used to estimate the effect of calcium supplementation on preeclampsia. Heterogeneity among included studies and publication bias were assessed using the I2 statistic and the Egger’s test, respectively.ResultsCalcium supplementation reduced the risk of preeclampsia by 47% (RR: 0.53, 95% CI: 0.42, 0.68) with a considerable level of heterogeneity (I2 = 84.39%). Our subgroup analyses revealed that the risk of preeclampsia was significantly lower in high-risk pregnancies that received calcium supplementation (RR: 0.35, 95% CI: 0.26, 0.47), indicating a 65% risk reduction. In comparison, low-risk pregnant women who received calcium supplementation experienced a 33% risk reduction (RR: 0.67, 95% CI: 0.59, 0.77). Furthermore, the effects of calcium supplementation were more pronounced in women from developing countries compared to those from developed countries.ConclusionThis umbrella review provides a summary of the evidence supporting the use of calcium supplementation to reduce preeclampsia. Incorporating calcium supplementation into antenatal care interventions may help to reduce the burden of preeclampsia and improve maternal and fetal outcomes. Further studies are needed to explore the impact of baseline calcium levels, optimal dosage, timing, and routes of supplementation to effectively decrease the incidence of preeclampsia.